Severe Metabolic Acidosis and Hepatopathy due to Leukoencephalopathy with Thalamus and Brainstem Involvement and High Lactate - Sellars, Elizabeth A.; Balmakund, Tonya; Bosanko, Katherine; Nichols, Brandi L.; Kahler, Stephen G.; Zarate, Yuri A. (Neuropediatrics, 2017)
Leukoencephalopathy with thalamus and brainstem involvement and high lactate (LTBL) is a recently described autosomal recessive mitochondrial disease characterized by early onset of neurological symptoms, a biphasic clinical course, and distinctive neuroimaging. Pathogenic variants in the EARS2 gene that encode for mitochondrial glutamyl-tRNA synthetase are responsible for LTBL. Here, we describe the clinical course of an infant diagnosed with an acute crisis of LTBL and severe liver disease. This article illustrates the utility of blood lactate quantification in addition to basic metabolic testing and brain imaging in a child with low tone and poor growth. In addition, this case demonstrates the utility of current genetic diagnostic testing, in lieu of more invasive procedures, in obtaining rapid answers in this very complicated group of disorders.
Keywords: leukoencephalopathy; LTBL; EARS2; lactic acidosis